Crystalline Silicon (c-Si) Solar Cell Interconnect Damage Prediction Function Based on Effect of Temperature Ramps and Dwells on Creep Damage under Field Thermal Cycling - Frank Kwabena Afriyie Nyarko; Gabriel Takyi; Anthony Agyei Agyemang; Charles Kofi Kafui Sekyere (Crystals, 2021)
c-Si solar cell interconnection damages from thermal cycles emanate from cumulative damage contributions from the various load steps in a typical thermal cycle. In general, a typical thermal cycle involves five thermal load steps, namely: 1st cold dwell, ramp-up, hot dwell, ramp-down, and 2nd cold dwell. To predict the contributions of each of these load steps to creep damage in soldered interconnections, each of the respective load steps needs to be profiled to accurately fit a function capable of predicting the damage contributions from a given number of thermal cycles. In this study, a field thermal cycle profile generated from in situ thermal cyclings at a test site in Kumasi, a hot humid region of sub-Saharan Africa, is used to predict damage in solar cell interconnections from accumulated creep energy density using finite element analysis (FEA). The damage was assessed for two different solder formulations, namely: Pb60Sn40 and Sn3.8Ag0.7Cu (lead-free). The results from the FEA simulations show that the cooling (ramp-down) load steps accounted for the highest accumulated creep energy density (ACED) damage in solder interconnections. The ramp-up load steps followed this closely. The cumulative contributions of the two load steps accounted for 78% and 88% of the total damage per cycle in the Pb60Sn40 and Sn3.8Ag0.7Cu solder interconnections, respectively. Furthermore, a study of the damage profiles from each of the five load steps revealed that each of the damage functions from the various load steps is a step function involving the first two thermal cycles, on one hand, and the remaining 10 thermal cycles on the other hand. The damage from the first two thermal cycles can be predicted from a logarithmic function, whereas the damage from the remaining 10 thermal cycles is predicted using six-order polynomial functions. The ACED results computed from the damage functions are in close agreement with the results from the FEA simulation. The functions generated provide useful relations for the prediction of the life (number of cycles to failure) of solder interconnections in solar cells. The systematic approach used in this study can be repeated for other test sites to generate damage functions for the prediction of the life of c-Si PV cells with SnPb and lead-free solder interconnections.